The administrative foundations of the Chinese fiscal state / Wei Cui, University of British Columbia. - Cui, Wei, 1970- (Cambridge tax law series., 2022)
On subjects ranging from trade to democratization, there has lately been a wave of laments about China's development belying Western expectations. Yet these disappointments often come with misunderstandings of the very institutions that China was expected to adopt. Chinese taxation offers a sharp illustration. When China introduced a tax system suited for the market economy, it fully intended tax collection to rely on self-assessment, audits, and the rule of law. But this Western approach was quickly jettisoned in favour of one that emphasized monitoring of taxpayers and ex ante interventions, at the expense of deterrence and truthful reporting norms. The Chinese approach surprisingly matches recommendations made by recent economic scholarship on tax compliance and state capacity. China's massive but little-known explorations in taxation highlight the distinct types of modern state capacity, and raise challenging questions about the future of taxation and the superiority of institutions based on rule of law.